Validation of the name Heliotropium shirazicum (Heliotropiaceae) - Negaresh, Kazem (Phytotaxa, 2018)
During the taxonomic revision of the genus Heliotropium Linnaeus (1753: 130) from Fars Province, S Iran, I came across few interesting specimens from the Bakhtegan Lake in Chahrig, Kharame. Critical studies with relevant literature revealed the identity of the collected specimens as Heliotropium shirazicum Mozaffarian (2006: 109). Unfortunately the name Heliotropium shirazicum was not validly published by Mozaffarian (2006), because, contrary to Art. 40 of ICN (McNeill et al. 2012), two specimens were indicated as “holotype”. Therefore, the name Heliotropium shirazicum is validated here by indicating a single specimen as the holotype.